2000
DOI: 10.1002/1097-0290(20001205)70:5<533::aid-bit8>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol utilization by sulfate‐reducing bacteria: An experimental and modeling study

Abstract: A mixed culture of sulfate-reducing bacteria containing the species Desulfovibrio desulfuricans was used to study sulfate-reduction stoichiometry and kinetics using ethanol as the carbon source. Growth yield was lower, and kinetics were slower, for ethanol compared to lactate. Ethanol was converted into acetate and no significant carbon dioxide production was observed. A mathematical model for growth of sulfate-reducing bacteria on ethanol was developed, and simulations of the growth experiments on ethanol wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
4
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 14 publications
3
31
4
7
Order By: Relevance
“…Total VFA and acetate concentrations were almost similar for all compartments. This may indicate that ethanol is converted to acetate, which may be further oxidized to CO 2 and H 2 O as previously reported in other studies [2,3,7,21]. The COD (Fig.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…Total VFA and acetate concentrations were almost similar for all compartments. This may indicate that ethanol is converted to acetate, which may be further oxidized to CO 2 and H 2 O as previously reported in other studies [2,3,7,21]. The COD (Fig.…”
Section: Resultssupporting
confidence: 78%
“…5) measurements showed that the remaining COD in the effluent of the reactor was due to acetate. Although serious acetate accumulation was not observed in the present study, acetate accumulation may take place at higher loadings as previously reported [2,3,7,[21][22][23]. Moreover, Sahinkaya et al [22] reported acetate oxidation is the limiting step in sulfate reducing bioprocesses.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations